1997
DOI: 10.1038/sj.onc.1200842
|View full text |Cite
|
Sign up to set email alerts
|

SEN6, a locus for SV40-mediated immortalization of human cells, maps to 6q26-27

Abstract: Normal cells show a limited lifespan in culture and the phenotype of cellular senescence. Tumors and tumor cell lines have typically overcome this form of growth suppression and grow continuously as immortal cell lines in culture. We have exploited the DNA virus SV40 to study the mechanism by which human ®broblasts overcome senescence and become immortal. Multiple steps have now been identi®ed, including inactivation of cellular growth suppressors through direct interaction with SV40 large T antigen and throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
38
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 47 publications
7
38
0
Order By: Relevance
“…As already mentioned, the senescence/immortalization gene SEN6 gene was recently assigned to a region de®ned by markers D6S133 and D6S281 (Banga et al, 1997). This is a rather large genomic interval which includes the region characterized in this report.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…As already mentioned, the senescence/immortalization gene SEN6 gene was recently assigned to a region de®ned by markers D6S133 and D6S281 (Banga et al, 1997). This is a rather large genomic interval which includes the region characterized in this report.…”
supporting
confidence: 51%
“…At variance with the fairly well characterized ovarian carcinomas (Zheng et al, 1991;Iwabuchi et al, 1995;Orphanos et al, 1995;Cooke et al, 1996;Sato et al, 1991, Saito et al, 1992Foulkes et al, 1993;Wan et al, 1994;Tibiletti et al, 1996) very few reports have investigated the involvement of chromosome 6 and, in particular of the long arm, in benign surface epithelial ovarian tumors (BOT) (Orphanos et al, 1995) We therefore decided to exploit the information derived from the cloning of the D6S149-D6S193 region to investigate by FISH analysis its integrity in a panel of benign ovarian tumors (BOTs). Besides the above considerations the rationale for this was the recent localization to 6q27, in a region de®ned by markers D6S133 and D6S281, of a locus for SV40-mediated immortalization of human cells (Sandhu et al, 1994;Banga et al, 1997). Assuming that a progression mechanism is at work in the tumorigenesis process leading to frank carcinomas as opposed to a di erentiation/maturation model (although this matter is still unsettled) (Liu and Nuzum, 1995;Zheng et al, 1995;Wolf et al, 1996;Salazar et al, 1997) the region mentioned above is expected to be altered in benign neoplasms.…”
mentioning
confidence: 99%
“…The possibility that another locus within 6q21-q23 also harbors a gene functioning as tumor suppressor for ovarian carcinoma cannot be ruled out. Indeed, the current evidence suggests that chromosome 6 contains several tumor suppressor genes important in these tumors (Banga et al, 1997;Cooke et al, 1996;Foulkes et al, 1993;Orphanos et al, 1995;Saha et al, 1995;Saito et al, 1992Saito et al, , 1996Tibiletti et al, 1998;Wan et al, 1994). More recently, Sandhu et al (1996) provided functional evidence for another candidate region on chromosome 6q important in ovarian tumorigenesis.…”
Section: Discussionmentioning
confidence: 96%
“…Of special interest is the finding of loss of 6q material. SEN6, a locus for SV40-mediated immortalization of human cells, maps to 6q26-q27, and has been demonstrated to be deleted in SV40 immortalized cells [23]. Experiments using microcell-mediated chromosome transfer demonstrated that chromosomes 1, 2, 4, 6, 7, and 11 can confer senescence in various tumor cell lines [24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%